2011
DOI: 10.5657/kfas.2011.44.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Moisture Content on the Growth and Gastrointestinal Evacuation of Sub-adult Olive Flounder Paralichthys olivaceus in the Summer and Winter Seasons

Abstract: Two experiments were conducted to investigate the effects of dietary moisture content on the growth and gastrointestinal evacuation of sub-adult olive flounder (Paralichthys olivaceus) in the summer and winter seasons. In the first experiment, three experimental diets containing different moisture levels (7%, 15%) and additives were prepared by adding water and commercial additives (1% nutrients, 1% digestives) to commercial extruded pellets. Fish (initial weight: 332 ± 9.2 g) were distributed randomly into si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…In this study, an increase in dietary moisture from 9% to 40% displayed no beneficial effects on the growth and feed utilization of olive flounder (106 g average initial weight). Similar nonsignificant differrences for the weight gain and feed efficiency were observed in the subadult flounder (332 g) fed diets containing 7-15% moisture under the rearing water temperature of 21°C, as well as in 646-g flounder fed between 8% and 23% moisture diets at the suboptimal water temperature of 12°C (Kim et al, 2011). Lee et al (2000b) reported that dietary moisture content displayed no significant effects on the weight gain or feed efficiency of Korean rockfish Sebastes schlegeli, but Chatzifotis et al (2005) reported that dentex Dentex dentex grew more effectively when receiving diets containing 20% moisture compared to 7% or 40% moisture levels.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In this study, an increase in dietary moisture from 9% to 40% displayed no beneficial effects on the growth and feed utilization of olive flounder (106 g average initial weight). Similar nonsignificant differrences for the weight gain and feed efficiency were observed in the subadult flounder (332 g) fed diets containing 7-15% moisture under the rearing water temperature of 21°C, as well as in 646-g flounder fed between 8% and 23% moisture diets at the suboptimal water temperature of 12°C (Kim et al, 2011). Lee et al (2000b) reported that dietary moisture content displayed no significant effects on the weight gain or feed efficiency of Korean rockfish Sebastes schlegeli, but Chatzifotis et al (2005) reported that dentex Dentex dentex grew more effectively when receiving diets containing 20% moisture compared to 7% or 40% moisture levels.…”
Section: Discussionsupporting
confidence: 69%
“…In this study, at 30 h postfeeding, the intestine of the flounder was primarily evacuated. However, subadult flounder (848 g) fed diets containing 8% and 23% moisture under a rearing water of 12°C required 56 h to evacuate their intestines in previous studies (Kim et al, 2011). The variations in gastric evacuation time may be due to differences in the fish size, the dietary composition, or the water temperature employed during these studies.…”
Section: Discussionmentioning
confidence: 94%